2006
DOI: 10.3171/foc.2006.21.6.8
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal and occipital peripheral nerve stimulation for craniofacial pain: a single-institution experience and review of the literature

Abstract: Object Treatment of chronic neuropathic pain in the region of the head and face presents a challenge for pain specialists; patients who do not respond to conventional treatment modalities usually continue to suffer from pain due to the lack of reliable medical and surgical approaches. Peripheral nerve stimulation (PNS) has been used to treat neuropathic pain for many decades, but only recently has it been applied systematically to the craniofacial region. To advance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(131 citation statements)
references
References 18 publications
7
120
0
2
Order By: Relevance
“…Consistent with prior reports, 6,11 we confirm that more than 70% of patients can expect to experience subjectively worthwhile pain relief with trigeminal stimulation. As with other pain-relieving modalities, loss of benefit over time is observed; however, long-term pain improvement can be seen in a significant subset of patients.…”
Section: Complicationssupporting
confidence: 80%
See 1 more Smart Citation
“…Consistent with prior reports, 6,11 we confirm that more than 70% of patients can expect to experience subjectively worthwhile pain relief with trigeminal stimulation. As with other pain-relieving modalities, loss of benefit over time is observed; however, long-term pain improvement can be seen in a significant subset of patients.…”
Section: Complicationssupporting
confidence: 80%
“…13 Over the next half century the use of peripheral nerve stimulation in the treatment of intractable facial pain has become increasingly reported. 1,6,7,[9][10][11][12] Significant advances in electrode construction, generator manufacturing, and surgical technique now allow for the permanent implantation of trigeminal branch electrodes by using minimally invasive methods. However, because very few practitioners routinely perform this procedure, the literature consists mainly of case reports and small case series.…”
mentioning
confidence: 99%
“…Location of this pocket is chosen based upon the patient's and surgeon's preference. Placement of the generator into the gluteal area, 49,50 abdominal wall, 38,44 or infraclavicular areas 34,45,47,48,51,55,58 has been described. In our opinion, the infraclavicular area (routinely used for placement of DBS generators) is the preferred location for both trigeminal and occipital nerve stimulation systems.…”
Section: Surgical Techniquementioning
confidence: 99%
“…The effects of GDNF treatment in 2 open-label trials generated much optimism that this molecule might provide neuroprotection as well as restorative benefits [31, 32]; however, a double-blind trial was halted due to lack of efficacy and the development of antibodies to GDNF in 10% of patients [33]. In concurrent experiments, it was found that some non-human primates exhibited cerebellar degeneration following GDNF withdrawal [34].…”
Section: Beyond Symptomatic Therapy: Neuroprotection Studies In Pdmentioning
confidence: 99%